Survey of Inmates of State Correctional Facilities and Census of State Adult Correctional Facilities, 1974 ([Verlag nicht ermittelbar], 1984)
The survey and census were part of a series of data collection efforts undertaken to assist policymakers in assessing and remedying deficiencies in the nation's correctional institutions. The survey was designed to provide information on social and economic characteristics of inmates, criminal and correctional background, court experience, and prison routine. The census gathered a wide range of information on all federal correctional facilities operating in 1974. The focus of the survey file is on the inmate, while the focus of the census file is on the facility.